Cinematic canines : dogs and their work in the fiction film - McLean, Adrienne L. (Rutgers University Press, 2014)
Dogs have been part of motion pictures since the movies began. They have been featured onscreen in various capacities, from any number of "man's best friends" (Rin Tin Tin, Asta, Toto, Lassie, Benji, Uggie, and many, many more) to the psychotic Cujo. The contributors to Cinematic Canines take a close look at Hollywood films and beyond in order to show that the popularity of dogs on the screen cannot be separated from their increasing presence in our lives over the past century.